The Princess who had no kingdom - "Ursula Jones" (London; Hachette children's group, 2009)
The story follows a princess who, despite lacking a kingdom, possesses a pony and cart, along with a red umbrella to shield her from the rain. Her true wealth lies in her kindness, cleverness, and beauty$1 (Bqualities that attract the attention of many princes. However, the narrative delves into the deeper question: what is a kingdom without love?s